Pengaruh Terpaan Konten Instagram @ezraalfatah Terhadap Motivasi Menyusun Skripsi (Studi Pada Followers @ezraalfatah) - Vera, Vera; Pradipta, Ade Devia; Joni, I Dewa Ayu Sugiarica (E-Jurnal Medium; Vol 6 No 1 (2025): Jurnal Ilmu Komunikasi Vol 6 No 1 Tahun 2025, 2025)
One of the educational content creator accounts on Instagram that appeared during Covid-19 was @ezraalfatah. @ezraalfatah is a content creator who discusses the world of education and shares tips and experiences so that they can graduate quickly. The study's goal is to explain how exposure to Instagram content @ezraalfatah affects students' motivation to write a thesis. This study uses S-O-R theory and uses quantitative explanatory analysis methods by distributing questionnaires to 100 respondents with criteria that have been determined. The results of this study show the influence of exposure to Instagram content @ezraalfatah on the motivation of students to compile a thesis with an R square obtained of 0.337. The influence of exposure to Instagram content @ezraalfatah on student motivation to compile a thesis by 33%, while 67% was influenced by other factors that were not studied in this study. Keywords: media exposure, content creator, Instagram @ezraalfatah, student motivation